2012
DOI: 10.1080/17290376.2012.665255
|View full text |Cite
|
Sign up to set email alerts
|

Factors underlying taking a child to HIV care: implications for reducing loss to follow-up among HIV-infected and -exposed children

Abstract: Objective: With the aim of reducing pediatric loss to follow-up (LTFU) from HIV clinical care programs in sub-Saharan Africa, we sought to understand the personal and socio-cultural factors associated with the behavior of caregivers taking HIV-infected and -exposed children for care in western Kenya.Methods: Between May and August, 2010, in-depth interviews were conducted with 26 purposively sampled caregivers caring for HIVinfected (7), HIV-exposed (17) and HIV-unknown status (2) children, documented as LTFU … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 27 publications
8
47
0
Order By: Relevance
“…The UNC-DRC program increased its efforts to track patients who missed appointments over the study period, but it does not appear that these efforts led to a reduction in the proportion of infants who were lost to follow-up. Research suggests that infants are less likely to be retained in care if their caregivers perceive them as healthy and more likely to be retained in care if they are identified as HIV-infected [42,43]. Thus, it is possible that the implementation of EID and the communication of initial negative test results, as well as the implementation of more effective prophylactic regimens, also affected the proportion of infants who were lost to follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The UNC-DRC program increased its efforts to track patients who missed appointments over the study period, but it does not appear that these efforts led to a reduction in the proportion of infants who were lost to follow-up. Research suggests that infants are less likely to be retained in care if their caregivers perceive them as healthy and more likely to be retained in care if they are identified as HIV-infected [42,43]. Thus, it is possible that the implementation of EID and the communication of initial negative test results, as well as the implementation of more effective prophylactic regimens, also affected the proportion of infants who were lost to follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Previously documented care obstacles include maternal disbelief of own HIV diagnosis, fear of involuntary HIV disclosure, anxiety regarding possible child HIV infection, unfriendly healthcare workers, poor parental education, poverty, inadequate family support and stigma (Donahue, Dube, Dow, Umar, & Van Rie, 2012;Horwood et al, 2010;Wachira, Middlestadt, Vreeman, & Braitstein, 2012). Integration of child health services, PMTCT and ART programmes is vital, and clear guidance to health workers is necessary in dealing with the confidentiality dilemma of maternal HIV infection in relation to documentation of relevant child information, including HIV exposure (Horwood et al, 2010;WHO, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some of the pediatricians practicing in the community refuse to perform or monitor the HIV screening protocol for their patients, and instead they prefer that these patients attend the screening clinic. An international qualitative study in Kenya analyzed the thematic content related to routinely taking children to HIV care (Wachira et al, 2013). They found that this decision involved multiple levels of intrapersonal, interpersonal, community and health system factors, which intertwined in complex ways to affect the decisions of Kenyan mothers to take their children to HIV care.…”
Section: Chapter Vi: Discussionmentioning
confidence: 99%
“…They found that this decision involved multiple levels of intrapersonal, interpersonal, community and health system factors, which intertwined in complex ways to affect the decisions of Kenyan mothers to take their children to HIV care. Even considering the remarkable differences in cultural, socioeconomic and health care for HIV disease environments between the U.S. and Kenya, Wachira's et al (2013) screening protocols for HIV-exposed infants by promoting maternal health behaviors for infant care could benefit from including at least some of these multi-level factors (Wachira et al, 2013).…”
Section: Chapter Vi: Discussionmentioning
confidence: 99%
See 1 more Smart Citation